2022
DOI: 10.3389/fchem.2022.941228
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Chemistry: The Role of Trimetaphosphate in Prebiotic Chemical Evolution

Abstract: Life’s origins have always been a scientific puzzle. Understanding the production of biomolecules is crucial for understanding the evolution of life on Earth. Numerous studies on trimetaphosphate have been conducted in the field of prebiotic chemistry. However, its role in prebiotic chemistry has been documented infrequently in the review literature. The goal of this thesis is to review the role of trimetaphosphate in the early Earth’s biomolecule synthesis and phosphorylation. Additionally, various trimetapho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…The size-controlling ability of phosphates was explored to demonstrate ATP-fueled transient membrane formation in the presence of phosphatases. Although phosphatases are likely to be absent in prebiotic environments, the hydrolysis of amino acid- N -triphosphate under ambient prebiotic conditions was reported. , Therefore, fuel-driven transient membrane formation under prebiotic conditions cannot be ruled out. Furthermore, we reported that the OLEA-ATP membrane is more stable in the presence of salt than the OLMEA-ATP membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The size-controlling ability of phosphates was explored to demonstrate ATP-fueled transient membrane formation in the presence of phosphatases. Although phosphatases are likely to be absent in prebiotic environments, the hydrolysis of amino acid- N -triphosphate under ambient prebiotic conditions was reported. , Therefore, fuel-driven transient membrane formation under prebiotic conditions cannot be ruled out. Furthermore, we reported that the OLEA-ATP membrane is more stable in the presence of salt than the OLMEA-ATP membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to higher solubility, unlike reactions using phosphates, phosphorylation using polyphosphates does not require the removal of water or hydroxyl groups, which means it can occur in aquatic conditions [ 20 ]. Trimetaphosphate could be the most studied polyphosphate, which can phosphorylate sugars, glyceric acid, amino acids, and nucleosides under moderate conditions [ 25 , 26 ]. A weakness of the polyphosphate-based pathway is that the corresponding minerals are rare on Earth.…”
Section: Source Of Materials Required For Atp Synthesismentioning
confidence: 99%
“…As early as 1871, Darwin recognized the relevance of phosphate in protein synthesis in the origin of life [13,14]. Phosphorus also plays a significant role in the regulation of chemical evolution under prebiotic settings, and contributes to the synthesis of amino acids, nucleosides and other life-related raw materials, making it an indispensable component of prebiotic synthesis [15,16]. The majority of phosphorus on early Earth was in the form of water-insoluble minerals like apatite, which became the primary source of phosphorus for the Earth's phosphorus cycle [17].…”
Section: Introductionmentioning
confidence: 99%